EKOSENTRISME MENGAWAL KEARIFAN ARSITEKTUR INDONESIA MENUJU PERADABAN MASA DEPAN: DISKURSUS - Ismail Ismail; Rita Laksmitasari Rahayu (Lakar: Jurnal Arsitektur, 2020)
Development in the built environment involves architects as planners. One of the architect's works is a high-rise building. High-rise buildings in Indonesia affect the social and cultural aspects of the community. Architectural works are present without forgetting environmental ethics. Anthropocentrism moves into ecosentrism which makes people aware that they cannot be separated from nature. The presence of buildings in the universe (macro cosmos) is the scope of modern science and the latest technology. The scientific method, with all its imperfections, can be used to improve social, political, and economic systems, and it continues to apply, whatever the improvement criteria that are applied. Indonesian architects must move toward ecocentric thinking with a localized value. Need awareness to cultivate modern science that can help humans. Processing modern science also maintains the universe for human interests in social, cultural values in addition to economic, technological and political values.